A mindset of competition versus cooperation moderates the impact of social comparison on self-evaluation - Colpaert, Lucie; Muller, Dominique; Fayant, Marie-Pierre; Butera, Fabrizio (Frontiers in Psychology, 2015)
Do people feel better or worse about themselves when working with someone who is better than they are? We present the first replication of the work of Stapel and Koomen (2005) who showed that being in a competitive vs. cooperative mindset moderates the effects of social comparison on self-evaluation. In Experiment 1, we present a close replication of Stapel and Koomen (2005, Study 2). Participants in competition/cooperation had to self-evaluate after receiving information about the personal characteristics of an upward/downward comparison target. In Experiment 2, we went further by providing feedback about both the comparison target and the self. Our results and a small-scale meta-analysis combining our experiments and Stapel and Koomen’s confirm that a competitive/cooperative mindset moderates the impact of social comparison on self-evaluation; nevertheless, the effect size we found across the two experiments is clearly more modest than the one found in Stapel and Koomen’s work.